Embedding QR codes onto B-spline surfaces for 3D printing. (September 2018) - Kikuchi, Ryosuke; Yoshikawa, Sora; Jayaraman, Pradeep Kumar; Zheng, Jianmin; Maekawa, Takashi
Abstract: Recent advance of Additive Manufacturing technologies allows us to manufacture various parts used in real-world products. Consequently, product tracking of such 3D printed parts is an important issue. Quick Response (QR) code which is a two-dimensional matrix barcode invented by Denso, a Japanese automotive industry, in 1994, can be used for this purpose. It can store more data than the 1D barcode in a smaller space, and using a smartphone as a scanner, one can directly visit a website where all the information of the parts is stored. However, QR codes require secondary procedures to add them to products and are also vulnerable to wear and tear. Moreover, QR codes cannot be added to freeform surfaces, but only to developable surfaces. In this paper we propose a novel technique to embed QR codes onto CAD models consisting of freeform surfaces represented by B-spline surfaces, which produces 3D QR codes. 3D QR codes work similar to 2D QR codes and can be read by existing QR scanners, but are designed by grooving the surface to obtain light and dark regions caused by ambient occlusion. Unlike conventional QR codes, 3D QR codes do not fall off from the part and can even be painted if necessary. Furthermore, we do not need to prepare dark-colored and light-colored materials for 3D printing as the dark color is provided by the grooving. We demonstrate the effectiveness of our technique with various examples. Graphical abstract: Highlights: A concept called 3D QR code that can be printed directly on parts is introduced. The method allows to print on parts represented in B-spline format. No secondary procedure in adding the code during the printing process is required. The dark color of the code is provided by ambient occlusion due to grooving.